Clinical and diagnostic utility of platelet count and its parameters in COVID-19 - Kevin Manuel; Marie Moses Ambroise; Anita Ramdas; Renu G’Boy Varghese; Natarajan Vasanthi; Kandasamy Ravichandran (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2024)
The majority of the published studies have described the alterations in platelet count and platelet indices in both severe and non-severe Coronavirus Disease 2019 (COVID-19). However, their association with COVID-19 mortality remains unclear. In the present study, our aim is to determine the temporal evolution of platelet count and its parameters between survivors and non-survivors, as well as their potential association with clinical outcomes. This cross-sectional study included 1118 inpatients (≥18 years old) diagnosed as SARS-CoV-2 positive by a Real-Time Polymerase Chain Reaction (RT-PCR) and hospitalized between May 1st, 2020 and November 1st, 2020. Data of complete blood count (CBC) parameters evaluated on different days after admission was gathered and the median value of each CBC parameter was considered for assessing the difference between survivors and non-survivors. There was statistically significant variation between survivors and non-survivors for platelet count [p<0.001, mean difference-80 x 109/L], mean platelet volume [p<0.001, mean difference- 0.7 fL], platelet distribution width [p<0.001, mean difference-2.5%] and platelet-lymphocyte ratio [p<0.001, mean difference-123.8]. Thrombocytopenia occurred more commonly in deceased patients compared to survivors. Platelet count, Mean Platelet Volume (MPV) and Platelet Distribution Width (PDW) differed significantly between survivors and non-survivors, revealing distinct trends indicating their importance in the management of COVID-19 patients. These cost-effective parameters can be easily obtained from a CBC.